ABCA1 69C>T Polymorphism and the Risk of Type 2 Diabetes Mellitus: A Systematic Review and Updated Meta-Analysis - Yoon, Ha Young; Lee, Min Hye; Song, Yubin; Yee, Jeong; Song, Gonjin; Gwak, Hye Sun (Frontiers in Endocrinology, 2021)
Background: The ATP-binding cassette transporter A1 (ABCA1) is likely associated with the risk of type 2 diabetes mellitus (T2DM) via β cell function modification, but the evidence on the association remains unclear. This study aimed to investigate the relationship between the ABCA1 69C>T polymorphism and the risk of T2DM through a systematic review and meta-analysis. Materials and Methods: The PubMed, Web of Science, and Embase databases were searched for qualified studies published until August 2020. Studies that included the association between the ABCA1 69C>T polymorphism and the risk of T2DM were reviewed. The odds ratios (ORs) and 95% confidence intervals (CIs) were evaluated. Results: We analyzed data from a total of 10 studies involving 17,742 patients. We found that the CC or CT genotype was associated with increased risk of T2DM than the TT genotype (OR, 1.41; 95% CI, 1.02-1.93). In the Asian population, the C allele carriers had a higher risk of T2DM than those with the TT genotype; the ORs of the CC and CT genotypes were 1.80 (95% CI, 1.21-2.68) and 1.61 (95% CI, and 1.29-2.01), respectively. Conclusions: This meta-analysis confirmed that the ABCA1 69C>T genotype showed a decrease risk of T2DM compared to the CC or CT genotypes.